2014
DOI: 10.1016/j.cam.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

(M,N)-coherent pairs of order(m,k)and Sobolev orthogonal

Abstract: a b s t r a c tA pair of regular linear functionals (U, V) is said to be a (M, N)-coherent pair of order (m, k) if their corresponding sequences of monic orthogonal polynomials {P n (x)} n≥0 and {Q n (x)} n≥0 satisfy a structure relation such as To be more precise, let us assume that m ≥ k. If m = k then U and V are related by a rational factor (in the distributional sense); if m > k then U and V are semiclassical and they are again related by a rational factor. In the second part of this work we deal with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…In addition, they showed that the linear functionals U and V satisfy the relation rðxÞU .ðxÞV, where rðxÞ and .ðxÞ non zero polynomials such that degðrðxÞÞ 3 and degð.ðxÞÞ 1. Finally, in a recent work by de Jesús et al [5], the more general case for coherence was characterized. They studied the structure relation …”
Section: A Matrix Characterization For the Coherence Of Orthogonal Pomentioning
confidence: 99%
“…In addition, they showed that the linear functionals U and V satisfy the relation rðxÞU .ðxÞV, where rðxÞ and .ðxÞ non zero polynomials such that degðrðxÞÞ 3 and degð.ðxÞÞ 1. Finally, in a recent work by de Jesús et al [5], the more general case for coherence was characterized. They studied the structure relation …”
Section: A Matrix Characterization For the Coherence Of Orthogonal Pomentioning
confidence: 99%
“…In [9], it was proved that if ðU; VÞ is an ðM; NÞ coherent pair of order m; m P 1, of positive definite linear functionals such that l 0 and l 1 are their corresponding positive Borel measures, then the SMOP fP n ðxÞg nP0 and fS n ðx; kÞg nP0 with respect to U and h ; i k , respectively, satisfy the algebraic relation (1.2). So, using the notation e a i;n ðn þ 1Þ m ðn i þ 1Þ m a i;n ; n P 0;…”
Section: A Matrix Interpretation Of Sobolev Orthogonal Polynomials Anmentioning
confidence: 99%
“…Indeed, when the linear functionals U and V are positive definite and l 0 and l 1 are the positive Borel measures associated with them, respectively, de Jesus, Marcellán, Petronilho, and Pinzón Cortés [9] showed that the ðM; NÞ coherence relation of order m (1.1), m P 1, implies…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations